Greater addition of neurons to the olfactory bulb than to the cerebral cortex of eulipotyphlans but not rodents, afrotherians or primates - Ribeiro, Pedro F. M.; Manger, Paul R.; Catania, Kenneth C.; Kaas, Jon H.; Herculano-Houzel, Suzana (Frontiers in Neuroanatomy, 2014)
The olfactory bulb is an evolutionarily old structure that antedates the appearance of a six-layered mammalian cerebral cortex. As such, the neuronal scaling rules that apply to scaling the mass of the olfactory bulb as a function of its number of neurons might be shared across mammalian groups, as we have found to be the case for the ensemble of non-cortical, non-cerebellar brain structures. Alternatively, the neuronal scaling rules that apply to the olfactory bulb might be distinct in those mammals that rely heavily on olfaction. The group previously referred to as Insectivora includes small mammals, some of which are now placed in Afrotheria, a base group in mammalian radiation, and others in Eulipotyphla, a group derived later, at the base of Laurasitheria. Here we show that the neuronal scaling rules that apply to building the olfactory bulb differ across eulipotyphlans and other mammals such that eulipotyphlans have more neurons concentrated in an olfactory bulb of similar size than afrotherians, glires and primates. Most strikingly, while the cerebral cortex gains neurons at a faster pace than the olfactory bulb in glires, and afrotherians follow this trend, it is the olfactory bulb that gains neurons at a faster pace than the cerebral cortex in eulipotyphlans, which contradicts the common view that the cerebral cortex is the fastest expanding structure in brain evolution. Our findings emphasize the importance of not using brain structure size as a proxy for numbers of neurons across mammalian orders, and are consistent with the notion that different selective pressures have acted upon the olfactory system of eulipotyphlans, glires and primates, with eulipotyphlans relying more on olfaction for their behavior than glires and primates. Surprisingly, however, the neuronal scaling rules for primates predict that the human olfactory bulb has as many neurons as the larger eulipotyphlan olfactory bulbs, which questions the classification of humans as microsmatic.